Education for mothers: Effect of Otaria Exercise on Superoxide Dismutase (SOD) Levels - Rafidah; Januarsih; Erni Yuliastuti; Ari Kusmiwiyati (Jurnal Penelitian Pendidikan IPA, 2025)
The postpartum period is a critical period susceptible to oxidative stress due to physiological, hormonal, and metabolic changes. One of the main antioxidant enzymes involved in combating oxidative stress is Superoxide Dismutase (SOD). Otaria gymnastics, a form of light physical exercise combining movement, breathing, and relaxation, is believed to increase the body's antioxidant capacity. This study aimed to determine the effect of Otaria gymnastics on SOD levels in postpartum mothers. The study used a quasi-experimental design with a pretest-posttest control group approach. The sample consisted of 30 postpartum mothers divided into an intervention group (n = 15) who performed Otaria gymnastics for 7 days and a control group (n = 15) without intervention. SOD levels were measured using spectrophotometry. The study showed a significant increase in SOD levels in the intervention group of 0.44 U/mL (p = 0.001), while the control group experienced a decrease of 0.16 U/mL (p = 0.021). The intergroup test showed a significant difference (p = 0.000). These findings indicate that Otaria Exercise is effective in increasing SOD levels and strengthening the body's antioxidant defenses in postpartum mothers. Otaria Exercise can be recommended as a simple non-pharmacological intervention in postpartum recovery programs to support maternal health holistically.